Law Enforcement against Environmental Pollution at PT Sugih Waras Jaya - Crystya Zuliana; Hanin Alya Labibah; Mohamad Yasir (Jurnal Hukum In Concreto, 2026)
This study examines the legal regulation of corporate environmental pollution under Law No. 32 of 2009 on Environmental Protection and Management and evaluates administrative law enforcement by the Environmental Agency of Tuban Regency against PT Sugih Waras Jaya. The research method used is a normative-empirical legal study employing statutory and case approaches. Data were obtained through interviews with relevant government officials and a review of legislation, legal literature, and academic journals. The findings indicate that the national legal framework clearly regulates corporate responsibility through environmental permitting obligations, the application of the precautionary principle, and the polluter pays principle as preventive instruments. However, in practice, administrative enforcement at the regional level still faces various challenges, including limited institutional capacity, a tendency to rely on persuasive approaches, and resistance from corporate actors. The enforcement process, which begins with public complaints and ends with administrative sanctions, has not yet been fully effective in creating a deterrent effect. These research findings highlight a gap between legal norms and practical implementation and underscore the importance of institutional strengthening and consistent enforcement to enhance environmental protection at the local level.